(untitled) (Swiss Medical Weekly, 2022)
High-level sports competition is popular among Swiss youth. Even though preparticipation evaluation for competitive athletes is widespread, screening strategies for diseases responsible for sudden death during sport are highly variable. Hence, we sought to develop age-specific preparticipation cardiovascular evaluation (PPCE) proposals for Swiss paediatric and adolescent athletes (under 18 years of age). We recommend that all athletes practising in a squad with a training load of at least 6 hours per week should undergo PPCE based on medical history and physical examination from the age of 12 years on. Prior to 12 years, individual judgement of athletic performance is required. We suggest the inclusion of a standard 12-lead electrocardiogram (ECG) evaluation for all post-pubertal athletes (or older than 15 years) with analysis in accordance with the International Criteria for ECG Interpretation in Athletes. Echocardiography should not be a first-line screening tool but rather serve for the investigation of abnormalities detected by the above strategies. We recommend regular follow-up examinations, even for those having normal history, physical examination and ECG findings. Athletes with an abnormal history (including family history), physical examination and/or ECG should be further investigated and pathological findings discussed with a paediatric cardiologist. Importantly, the recommendations provided in this document are not intended for use among patients with congenital heart disease who require individualised care according to current guidelines.